Comprehensive Multiomic Analysis Reveals Metabolic Reprogramming Underlying Human Fontan‐Associated Liver Disease - Rasheed Sule; Po Hu; Clarissa Shoffler; Christopher Petucci; Benjamin J. Wilkins; Jack Rychik; Liming Pei (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The Fontan operation is the current standard of care for single‐ventricle congenital heart disease. Almost all patients with Fontan operation develop liver fibrosis at a young age, known as Fontan‐associated liver disease (FALD). The pathogenesis and mechanisms underlying FALD remain little understood, and there are no effective therapies. We aimed to present a comprehensive multiomic analysis of human FALD, revealing the fundamental biology and pathogenesis of FALD. Methods and Results We recently generated a single‐cell transcriptomic and epigenomic atlas of human FALD using single‐nucleus multiomic RNA sequencing and assay for transposase‐accessible chromatin using sequencing, which uncovered substantial metabolic reprogramming. Here, we applied liquid chromatography–mass spectrometry–based untargeted metabolomics to unveil the metabolomic landscape of human FALD, using liver samples/biopsies from age‐ and sex‐matched donors and patients with FALD (n=12 per group). Results were integrated with liver single‐nucleus multiomic RNA sequencing and assay for transposase‐accessible chromatin using sequencing and serum metabolomics data to present a comprehensive multiomic atlas of FALD.We discovered significant metabolic abnormalities in livers of adolescent patients with Fontan circulation, particularly amino acid metabolism, peroxisomal fatty acid oxidation, cytochrome P450 system, glycolysis, tricarboxylic acid cycle, ketone body metabolism, and bile acid metabolism. Integrated analyses with liver single‐nucleus multiomic RNA sequencing and assay for transposase‐accessible chromatin using sequencing results unveiled potential underlying mechanisms of these metabolic changes. Comparison with serum metabolomics data indicate that liver metabolic reprogramming contributes to circulatory metabolomic changes in FALD. Furthermore, comparison with metabolomics data of human metabolic dysfunction–associated fatty liver disease and metabolic dysfunction–associated steatohepatitis highlighted dysregulated amino acid metabolism as a common metabolic abnormality. Conclusions Our comprehensive multiomic analyses reveal new insights into the fundamental biology and pathogenesis mechanisms of human FALD.